Penyalahgunaan Narkoba Di Kalangan Remaja Kota Tanjung Pinang - Amelia Frista Meliyana; Totok Minto Leksono; Andi Nashwa Intan Salam; Indah Syifa Rahma Sari; Metasari Putri (Institut Riset dan Pengembangan Indonesia, 2024)
Drug abuse among adolescents is an act that is not in accordance with social norms and values ​​that apply in society. Deviance occurs when a person or group of people does not comply with the norms or standards and values ​​that have been applied in society. The cause of drug abuse among adolescents is caused by internal factors and external factors. Internal factors, namely factors that come from a person, where the internal factors themselves consist of Personality Factors, Family Factors and Economic Factors. While External Factors, namely factors that come from outside a person or teenager that affect the occurrence of drug abuse. The external factor itself consists of factors of association and social factors of society. This study aims to determine what is the most dominant factor that influences drug abuse among teenagers. The data obtained in this study can be divided into primary data and secondary data and analyzed qualitatively by providing an overview of information. From the results of research that has been carried out, it can be concluded that the most dominant factor that causes drug abuse among adolescents is due to social factors, this is based on the conclusions from direct interviews from informants who stated that the factor of association with peers who were too free and uncontrolled causes teenagers to fall into drug abuse. So that teenagers do not fall into drug abuse, parental participation is needed by further increasing supervision of the behavior of their family members, parents are also expected to always take the time to always be by their children's side in any condition, so that teenagers do not fall into doing things that deviant, especially drug abuse. In addition, it is necessary to have good cooperation by all elements of both the government and society so that drug abuse among teenagers can be prevented as early as possible.